Identifikasi Masalah pada Proses Pembelajaran Jarak Jauh secara Online yang dihadapi Guru-Guru Selama Pandemi (Studi Kasus: Guru-Guru SMP Negeri 1 Merek) - Bernadetta Br Haloho; Diah Priharsari; Satrio Agung Wicaksono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Currently the face-to-face learning process can no longer be carried out due to the 2019 coronavirus disease (covid-19) pandemic which has spread in Indonesia. The spread of Covid-19 has a major impact, especially on the education sector. The temporary closure of educational institutions is an effort to contain the spread of the Covid-19 pandemic. Teachers at SMP Negeri 1 Merek also experienced the same thing, most of whom were unfamiliar with the use of technology. Habits in the face-to-face learning process make teachers experience many obstacles in teaching online. Some teachers when they try to use technology for the first time are successful, but they forget to repeat the same thing on a different day. This descriptive study is expected to produce an explanation of the results of the analysis based on the exploration carried out. Exploration is carried out by means of interviews to explore teacher experiences during the online distance learning process. The results of the interviews with seven resource persons were then made transcripts and analyzed by thematic coding, in order to obtain the appropriate theme / categorization. It is hoped that this research will produce documentation that can be used to find out what was experienced by the teachers and what technology was used during the online distance learning process. Based on the research that has been done, teachers at SMP Negeri 1 Merek use whatsapp and classroom applications.